Fabrication of ultra-dense sub-10 nm in-plane Si nanowire arrays by using a novel block copolymer method: optical properties. Issue 4 (5th January 2016) - Ghoshal, Tandra; Ntaras, Christos; O'Connell, John; Shaw, Matthew T.; Holmes, Justin D.; Avgeropoulos, Apostolos; Morris, Michael A.
Abstract : The use of a low- χ, symmetric block copolymer as an alternative to the high- χ systems currently being translated towards industrial silicon chip manufacture has been demonstrated. Abstract : The use of a low- χ, symmetric block copolymer as an alternative to the high- χ systems currently being translated towards industrial silicon chip manufacture has been demonstrated. Here, the methodology for generating on-chip, etch resistant masks and subsequent pattern transfer to the substrate using ultra-small dimension, lamellar, microphase separated polystyrene- b -poly(ethylene oxide) (PS- b -PEO) block copolymer (BCP) is described. Well-controlled films of a perpendicularly oriented lamellar pattern with a domain size of ∼8 nm were achieved through amplification of an effective interaction parameter ( χ eff ) of the BCP system. The self-assembled films were used as 'templates' for the generation of inorganic oxides nanowire arrays through selective metal ion inclusion and subsequent processing. Inclusion is a significant challenge because the lamellar systems have less chemical and mechanical robustness than the cylinder forming materials. The oxide nanowires of uniform diameter (∼8 nm) were isolated and their structure mimics the original BCP nanopatterns. We demonstrate that these lamellar phase iron oxide nanowire arrays could be used as a resist mask to fabricate densely packed, identical ordered, good fidelity silicon nanowire arrays on the substrate. Possible applications of the materials prepared are discussed, in particular, in the area of photonics and photoluminescence where the properties are found to be similar to those of surface-oxidized silicon nanocrystals and porous silicon.